The Effect of Mindfulness-Based Intervention on Work Stress of Nurses who Work in an Emergency Department in a Hospital in Indonesia - Dhevy Puswiartika; Bau Ratu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Being a nurse is a stressful profession due to the daily heavy and demanding work. Mindfulness can be effective to teach nursing personnel how to cope with such stress. The intervention “Don’t Worry, Be Mindful” was developed by the researchers for the Indonesian situation based on the concept of Mindfulness-Based Stress Reduction (MBSR). We explored its effect in an exploratory pre-post design with 15 experienced members from the nursing personnel at the Emergency Department of a peripheral hospital in Pandeglang, Banten, Indonesia. The results showed that after the “Don’t Worry, Be Mindful” intervention the participant’s stress level was significantly reduced. Each of the nurses showed less stress at the post-test than at the pretest. This outcome indicated that mindfulness-based intervention is a promising tool to reduce stress in nursing personnel in a peripheral hospital in the less developed part of South-East country like Indonesia.Profesi perawat merupakan profesi yang penuh tekanan karena tuntutan pekerjaan sehari-hari yang berat. Mindfulness terbukti efektif untuk membantu perawat dalam mengatasi stres kerja. Intervensi “Don’t Worry, Be Mindful” dikembangkan oleh peneliti untuk konteks Indonesia berdasarkan konsep Mindfulness Based Stress Reduction (MBSR). Peneliti melakukan eksplorasi terhadap efek intervensi mindfulness terhadap stres kerja perawat dengan menggunakan desain pre-post test dengan partisipan 15 orang perawat pada Unit Gawat Darurat (UGD) rumah sakit di Pandeglang, Banten, Indonesia. Hasil penelitian ini menunjukkan bahwa setelah pemberian intervensi "Don’t Worry, Be Mindful" diketahui bahwa tingkat stres partisipan berkurang secara signifikan. Setiap perawat menunjukkan tingkat stres yang menurun pada saat post-test, apabila dibandingkan dengan tingkat stres perawat saat pretest. Hasil ini menunjukkan bahwa intervensi berbasis mindfulness merupakan salah satu teknik yang efektif untuk mengurangi stres pada perawat di rumah sakit di Indonesia.